Survei Gerak Dasar Lokomotor dan Manipulatif Siswa Kelas IV SD - Mashudi, Abdul Rohman; Nurrochmah, Siti (Sport Science and Health, 2020)
The purpose of this study was to determine the development of basic locomotor and manipulative movements of students through the 30 meter running test, long jump without prefix, vertical jump, catch the ball and throw the ball at the goal using the target. The results of the research data on the ability of basic locomotor motion using the 30 meter running test were in the good category totaling 12 students. The ability to move long jump without prefix was in the very good category amounting to 17 students and the ability to move upright (vertical jump) was in the medium category and not good amounting to 14 students. Meanwhile, the ability of manipulative movement using the throw and catch test was in the bad category, amounting to 17 students. The ability to throw the ball at the goal using the target is in the medium category amounting to 10 students.Â Tujuan penelitian ini adalah untuk mengetahui perkembangan gerak dasar lokomotor dan manipulatif siswa melalui tes lari 30 meter, loncat jauh tanpa awalan, loncat tegak, lempar tangkap bola dan lempar bola ke gawang menggunakan sasaran. Hasil data penelitian kemampuan gerak gerak dasar lokomotor menggunakan tes lari 30 meter berada pada kategori baik berjumlah 12 siswa. Kemampuan gerak loncat jauh tanpa awalan berada pada kategori baik sekali berjumlah 17 siswa dan kemampuan gerak loncat tegak (vertical jump) berada pada kategori sedang dan kurang baik berjumlah 14 siswa. Sedangkan kemampuan gerak manipulatif menggunakan tes lempar tangkap berada pada kategori tidak baik berjumlah 17 siswa. Kemampuan lempar bola ke gawang menggunakan sasaran berada pada kategori sedang sebesar berjumlah 10 siswa.